(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we investigate the entire solutions for a certain class of non-linear difference equations of the form: f^n+ q(z)e^Q(z)L_1(z, f) = α_1(z)e^β_1(z)+α_2(z)e^ β_2(z), where L_1(z, f) is the generalized linear difference operator, α_1(z) and α_2(z) are non-zero small functions of f, q(z) and Q(z)(nonconstant), β_1(z) and β_2(z) are non-zero polynomials. Our results improve upon and generalize some previously established findings.